Socio-demographic Factors Associated with Emergency Caesarean Section Cases admitted at Tertiary Care Hospital in Dhaka City - Sultana, Rifat; Banu, Dewan Shahida; Khatun, Mahmuda; Dolon, Fatima; Nahar, Mahmuda; Sultana, Nasrin (Journal of Current and Advance Medical Research, 2018)
Background: Socio-demographic factors are related with the need of emergency obstetric care. Objectives: The purpose of the present study was to see the socio-demographic characteristics of emergency caesarean section. Methodology: This cross-sectional of study was conducted in the Department of Obstetrics and Gynaecology at Dhaka Medical College, Dhaka from the duration July 2006 to December 2006 for a period of six (6) months. The pregnant women underwent emergency caesarean section admitted at Dhaka Medical College Hospital during the mentioned period of the study were my study population. The cases were selected from the patients who got admitted at obstetrics ward of DMCH with an indication of emergency caesarean section with stable general condition at that moment. Every 10th patient was selected for the study. Data has been collected after taking written consent from the patients as per consent form. Then a thorough history, clinical examination was done and information were collected. Intraoperative complications such as haemorrhage, cardiac arrest were noted. Result: The study was performed on 100 cases of which 35(35.0%) emergency caesarean section cases belonged to the age group of 20 to 24 years and 56.0% were from lower socio economic class. Among them 42.0% of the cases of emergency caesarean section had education SSC and above level; furthermore 12.0% were illiterate. In addition 92.0% cases were house wife. Conclusion: In conclusion young house wives from lower socio economic status are mostly underwent emergency caesarean section. Journal of Current and Advance Medical Research 2017;4(1):23-26